Interfering Role of ERα on Adiponectin Action in Breast Cancer - Naimo, Giuseppina Daniela; Gelsomino, Luca; Catalano, Stefania; Mauro, Loredana; Andò, Sebastiano (Frontiers in Endocrinology, 2020)
Obesity is characterized by an excess of adipose tissue, due to adipocyte hypertrophy and hyperplasia. Adipose tissue is an endocrine organ, producing many bioactive molecules, called adipokines. During obesity, dysfunctional adipocytes alter adipokine secretion, contributing to pathophysiology of obesity-associated diseases, including metabolic syndrome, type 2-diabetes, cardiovascular diseases and many types of malignancies. Circulating adiponectin levels are inversely correlated with BMI, thus adiponectin concentrations are lower in obese than normal-weight subjects. Many clinical investigations highlight that low adiponectin levels represent a serious risk factor in breast carcinogenesis, and are associated with the development of more aggressive phenotype. A large-scale meta-analysis suggests that BMI was positively associated with breast cancer mortality in women with ERα-positive disease, regardless menopausal status. This suggests the importance of estrogen signaling contribution in breast tumorigenesis of obese patients. It has been largely demonstrated that adiponectin exerts a protective role in ERα-negative cells, promoting anti-proliferative and pro-apoptotic effects, while controversial data have been reported in ERα-positive cells. Indeed, emerging data provide evidences that adiponectin in obese patients behave as growth factor in ERα-positive breast cancer cells. This addresses how ERα signaling interference may enhance the potential inhibitory threshold of adiponectin in ERα-positive cells. Thus, we may reasonably speculate that the relatively low adiponectin concentrations could be still not adequate to elicit, in ERα-positive breast cancer cells, the same inhibitory effects observed in ERα-negative cells. In the present review we will focus on the molecular mechanisms through which adiponectin affects breast cancer cell behavior in relationship to ERα expression.